José Venturelli, Pioneer in Chile-China Relations: From Cultural Diplomacy to Non-State Actor; [José Venturelli, Pionero en Las Relaciones Chile-China: Desde la Diplomacia Cultural a Actor No Estatal] - Ahumada-Figueroa, M (Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura, 2024)
Chile and China’s diplomatic relations converged within the figure of José Venturelli, who, in a pioneering manner, saw China as a model to follow. This fact contains relevant aspects since his figure, as an artist and intellectual, was controversial and invisibilized by virtue of his radical commitment to the Asian country. This article attempts to inquire about his trajectory as a muralist-painter; his radical compromise with the People’s Republic of China from the conceptual approach of cultural diplomacy; his political contacts with the Communist Party, and his role as a non-state actor with residences in Chile, China, Cuba and Sweden. The analysis is addressed from the perspective of cultural diplomacy and non-State actors, who intervene in constructing new spaces for discussion. © 2024 Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura. All rights reserved.